Design ND Development of Knowledge Portal: Higher Secondary Education Sector - Miri, Santosh Kumar; Sahu, Neelam (International Journal of Computer Sciences and Engineering, 2025)
Day by day utilities of portals are increasing. Portal is batter to the website. I decide that I will develop the knowledge portal for HSE sector. Higher secondary education sector is backbone of Indian education. Streams, syllabus, question papers, e-Books, Notes, video lectures, study tips etc. are major parts of the developing educational portal. The aim of this portal will share the knowledge to the students, teachers as well as parents. It will help to the learners of both Hindi and English mediums. HTML, PHP, CSS, Java scripts, XAMPP and My SQL are useful tools for design and development of this portal. The name of database is hses. sql. All web pages and images of this portal are stored in the CVRU directory. All secondary education requirements are arranging in this portal. In this research paper, we will identify the best higher secondary education